On Generalization of the Pareto Distribution - Olapade, A. K. (2014)
In this paper, we present a probability density function that generalizes the Pareto distribution. The cumulative distribution function and the moments of the generalized distribution are obtained while the distribution of some order statistics of the distribution are established. Included in this paper are the estimation of the parameters of the generalized Pareto distribution and some theorems that relate it to other statistical distributions are established.